Prácticas de gestión del talento humano en empresas del Valle del Cauca (2015)
People and knowledge accumulated by an organization and how to use them, of major impact in this globalized world. For this reason, in order to establish competitive differentiation, a key factor lies in the management the organization and how it establishes its human talent. Research about the role, challenges and practices of 25 Cauca companies regarding management of human talent was developed (GTH), showing the approaches, models used and the role played by human management areas as strategic business partners. From this, many firms change from an operational approach to a strategic approach that adds value. The main challenges that these companies have confronted can be identified, showing that industrial relations, welfare programs, measuring the effectiveness of human talent and outsourcing processes are sensitive issues in many Colombian companies. These results suggest that to remain competitive, organizations should worry about improving their practices so that they attract, develop and retain human talent that is becoming more scarce and diverse